Aids in Infants and Children - Sunarto Sunarto (Paediatrica Indonesiana, 2019)
Children are infected by HIV, 80% vertically, from HIV infected mothetS mostly near or at delivery. Because heterosexual transmission of HIV among adults is more and more important it is estimated that at the end of this century there will be totally more than 10 million HIV infected children.